2017
DOI: 10.1101/128173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Δ9-THC and cannabidiol vapor inhalation in male and female rats

Abstract: Previous studies report sex differences in some, but not all, responses to cannabinoids in rats.The majority of studies use parenteral injection, however most human use is via smoke inhalation and, increasingly, vapor inhalation. The aim of this study was to compare thermoregulatory and locomotor responses to inhaled ∆ 9 -tetrahydrocannabinol (THC), cannabidiol (CBD) and their combination using an e-cigarette based model in male and female rats.Groups of male and female Sprague-Dawley rats (N=8 per group) were… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
110
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(130 citation statements)
references
References 70 publications
(85 reference statements)
19
110
1
Order By: Relevance
“…under conditions under which males do not (Wiley, 2003), that female rats develop tolerance to THC-induced errors on a learning task more slowly than males during chronic injection of 10 mg/kg THC, i.p., (Weed, Filipeanu, Ketchum & Winsauer, 2016) and that female rats develop a greater degree of nociceptive tolerance to THC even when the repeated dose is only 71% as large as the male dose (Wakley, Wiley & Craft, 2014). The study also demonstrated, as in our prior reports (Javadi-Paydar, Nguyen, Grant, Vandewater, Cole & Taffe, 2017;, that so long as intervals of at least 7 days are maintained between THC administration sessions, there is no detectable plasticity of the hypothermic response.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…under conditions under which males do not (Wiley, 2003), that female rats develop tolerance to THC-induced errors on a learning task more slowly than males during chronic injection of 10 mg/kg THC, i.p., (Weed, Filipeanu, Ketchum & Winsauer, 2016) and that female rats develop a greater degree of nociceptive tolerance to THC even when the repeated dose is only 71% as large as the male dose (Wakley, Wiley & Craft, 2014). The study also demonstrated, as in our prior reports (Javadi-Paydar, Nguyen, Grant, Vandewater, Cole & Taffe, 2017;, that so long as intervals of at least 7 days are maintained between THC administration sessions, there is no detectable plasticity of the hypothermic response.…”
Section: Discussionsupporting
confidence: 87%
“…Significant tolerance was observed only following the 7 th session of a twice daily regimen in female rats, and this was the case when the inhalation drug concentration was either 200 or 100 mg/mL THC in the PG. Similar to what has been previously shown (Javadi-Paydar, Nguyen, Grant, Vandewater, Cole & Taffe, 2017;, no substantial tolerance was observed when repeated THC inhalation sessions are spaced by at least 7 days, since the magnitude of the body temperature effect was similar to Sessions 4-5 of Study 2 in two additional THC inhalation sessions conducted at weekly intervals after the chronic THC week as well as during all of the vehicle pretreatment / THC inhalation conditions of Study 3 (Figure 4). This study also confirms that the hypothermic and antinociceptive responses to inhaled THC are mediated by, at least in part, CB 1 receptor function.…”
Section: Discussionsupporting
confidence: 85%
“…Significant tolerance was observed only following the 7 th session of a twice daily regimen in adult female rats, consistent with our prior report in which rectal temperature was sampled only after the 1 st and 7 th sessions and with our report of a similar timecourse of tolerance development in adolescent female rats (Nguyen et al, 2020). We have previously shown that no substantial thermoregulatory tolerance is observed when THC inhalation sessions are spaced by at least 7 days (Javadi-Paydar et al, 2017;Nguyen et al, 2016b) and this was confirmed more directly here since the repeated-exposure animals developed no additional tolerance to intermittent THC challenges (see Supplemental Figure S3). Despite this tolerance, presumably mediated at least in part by a down regulation of CB1 mediated signaling, the SR141716 pre-treatment produced a similar result as in the other groups, i.e.…”
Section: Figures 3 and Supplementalsupporting
confidence: 92%
“…This study used a clinically relevant and effective rodent co-exposure model of e-cigarette THC exposure and alcohol to examine the consequences of prenatal co-exposure. Vapor inhalation paradigms that deliver THC using commercially available e-cigarettes have recently been used in rodents to expose non-pregnant rats (Javadi-Paydar et al, 2019;Javadi-Paydar et al, 2018;Nguyen et al, 2019), but the use of such a model in pregnant rats is more limited (Weimar et al, 2020). To date, a rodent vapor inhalation paradigm for co-exposure to alcohol and cannabis during pregnancy has not been utilized.…”
Section: Introductionmentioning
confidence: 99%